Math, asked by abhay26royaltyfam, 10 months ago

21. Find the product
(i) (x + 1) (2x – 1) (x + 3)​

Answers

Answered by aryan073
1

Step-by-step explanation:

(1) x(2x-1)+1(2x-1)(x+3)

(2x²+x-1)(x+3)

2x²(x+3)+x(x+3)-1(x+3)

2x³+6x²+x²+3x-x-3=0

2x³+7x²+2x-3=0

Answered by sare83
0

Answer:

(x+1)(2x-1)(x+3) = 2x³+7x²+2x-3

Step-by-step explanation:

Given that,

(x+1)(2x-1)(x+3)

⇒ (2x²-x+2x-1)(x+3)

⇒ (2x²+x-1)(x+3)

⇒ (2x³+x²-x+6x²+3x-3)

⇒ 2x³+7x²+2x-3

∴ (x+1)(2x-1)(x+3) = 2x³+7x²+2x-3

HOPE THIS WOULD BE HELPFUL FOR YOU

Similar questions